Ratna Widiawati (10030151) Pengaruh Komunikasi Interpersonal Keluarga dan Motivasi Belajar terhadap Hasil Belajar IPS Siswa Kelas VII SMP N 3 SUTERA - Widiawati, Ratna - (STKIP PGRI Sumbar, 2014)
The purposes of research are to know as far as The affection of family interpersonal communication and study motivation to study result VII â social class student SMP N 3 SUTERA. The type of is an corelation research, The population of this research is VII â social class student parents ammount to 60 person.Where as the technical of sample making has done with pourposive sampling. Data collection technical has used questionnaire. Before has used to acquire data, questionnaire has validity test and analysis data technical has used descriptive analysis and inductive analysis. To examine hypothesis has used F- test and T- test.The result of research at belief level 95 % to indicate there are effect significant between family interpersonal communication to study result social studies VII social â class student SMP N 3 SUTERA because T- rule > T- table (4,199 > 2,000), The connection of family interpersonal communication and study result VII- social class student SMP N 3 SUTERA included medium (r = 0, 483) and contribution has given as big as 23,3 %. Because T- rule > T- table ( 8, 740> 2,000). The connection of study motivation with study result VII â social class student SMP N 3 SUTERA include powerfull (r = 0, 754) and contribution has given as 56,8 %. There are effectan significant between family interpersonal communication and study motivation together to study result VII â social class student SMP N 3 SUTERA, Because F- rule > F â table (37,554 > 3,17). The connection of family interpersonal communication and study motivation student with study result VII social â class student SMP N 3 SUTERA include medium (r= 0,754) and contribution has given as 56, 9 %.